Research and Application of Node.js Core Technology - Huang, Xiaoping (2020 International Conference on Intelligent Computing and Human-Computer Interaction (ICHCI), 2020)
Web development companies and developers can choose a variety of technology stacks to build Web applications. In the early days of network development, different technologies were used for front-end and back-end development. With the release of node.js, the construction of the website has undergone tremendous changes. Unlike single-threaded PHP and multi-threaded JAVA, a server programming platform based on the Chrome V8 engine JavaScript runtime environment-node.js came into being. Node.js uses its own built and defined attributes to make up for the shortcomings of the background development language in the traditional sense. It is a server-side JavaScript interpreter, which is used to conveniently build web applications with fast response speed and easy expansion. Node.js, with its event-driven, time loop mechanism, and non-blocking I/O model, can realize functions that Core JavaScript does not have or are not perfect, such as file systems, modules, packages, operating system APIs, and network communications. Historically, there has been more than one plan to port JavaScript outside the browser, but Node.js is the best one.